Menelusuri Jejak Kuliner Tembayat dalam Serat Centhini - Minardi, Minardi; Samidi, Samidi; Rahmah, Yulinar Aini (Manuskripta, 2021)
This study aims to determine the kinds or variety of food that was in Tembayat listed in Serat Centhini. In explaining about the political atmosphere during the manufacture of Serat Centhini, researchers using the Theory of Soft Power by Joseph Nye. The resulting conclusion that there are around 48 the name of the food that is written in the serat Centhini. The condition of this culinary've rarely heard by the public, the bias is said to have been a rare occurrence in Tembayat. About the political atmosphere, Serat Centhini was written by the candidate Pakubuwana V, while the father that Pakubuwana IV still reigned in the Kraton Kasunanan Surakarta Hadiningrat. Current conditions, Kraton Surakarta besieged by Pura Mangkunegaran, the Palace of the Sultanate Ngayogyakarta and the Netherlands, or better known as Pakepung. Then to raise the prestige or name Kraton Surakarta then this paper to be a form of resistance from Surakarta. Since that time, no paper work, as complete as that by loading all the potential of the Island of Java, it is often referred to as the Encyclopedia of Java. === Penelitian ini bertujuan untuk mengetahui macam atau aneka ragam kuliner yang berada di Tembayat yang tercantum dalam Serat Centhini. Dalam menjelaskan tentang suasana politik saat pembuatan Serat Centhini, peneliti menggunakan Teori Soft Power dari Joseph Nye. Kesimpulan yang dihasilkan bahwa terdapat sekitar 48 nama kuliner yang ditulis di Serat Centhini. Kondisi kuliner ini sudah jarang didengar oleh masyarakat, bisa dikatakan sudah langka keberadaanya di Tembayat. Mengenai suasana politik, Serat Centhini ditulis oleh calon Pakubuwana V, saat ayahanda yaitu Pakubuwana IV masih bertahta di Kraton Kasunanan Surakarta Hadiningrat. Kondisi saat itu, Kraton Surakarta dikepung oleh Pura Mangkunegaran, Kraton Kasultanan Ngayogyakarta dan Belanda atau lebih dikenal sebagai Pakepung. Maka untuk menaikkan pamor atau nama Kraton Surakarta maka karya tulis ini menjadi bentuk perlawanan dari Surakarta. Karena zaman itu, belum ada karya tulis yang selengkap itu dengan memuat semua potensi yang dimiliki Pulau Jawa, maka sering disebut sebagai Ensiklopedia Jawa.